A Systematic Review of Women's Knowledge and Practices Regarding Breast Self-Examination - Sianipar, Berlian Kando; Panduragan, Santhna Letchmi; Situmorang, Ronalen Br (International Journal of Nursing Information, 2024)
Globally, breast cancer is the primary cause of death. Non-pharmacological therapy involving knowledge and practice of breast self-examination (BSE) is a straightforward, incredibly affordable, non-invasive initial diagnostic technique for early breast cancer diagnosis. The objective of this study is to examine women's knowledge and practices about breast self-examination. The method is a systematic review using PRISMA. Data sourced from searches in PubMed, ScienceDirect, and Google Scholar were conducted to identify relevant published studies. The data was restricted to English-language articles on women's knowledge and practice of breast self-examination published during the previous five years. The results show 15 articles that explain the knowledge and practice of breast self-examination carried out by women. The majority of women have heard of BSE but do not fail to carry out BSE regularly every month. The majority of evaluated studies demonstrated a notable correlation between participants' knowledge of breast cancer and their age, marital status, and level of education. The conclusion is that women's knowledge and practice of breast self-examination are still lacking. Hence, it is imperative to develop techniques that might enhance the awareness and adoption of breast self-examination. Although breast self-examination is generally part of a prevention and monitoring strategy, it does not replace medical or pharmacological care. The contribution of this study is to provide information that breast self-examination has several important contributions in the context of breast health and early detection of breast cancer.